Plume tectonics – Myth or Reality? - Daragan-Sushchov Yurii I. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Санкт-Петербургский горный университет», 2017)
The paper is dedicated to the role of mantle plumes in the formation of large igneous provinces. From different regions of the world facts are mentioned that contradict key points of plume tectonics. Closer attention is paid to classical volcanic provinces on Hawaiian islands and in Iceland, as well as to Siberian and Deccan Traps, oceanic plateau Ontong Java, Central Atlantic magmatic province, Alfa and Mendeleev Ridges in the Arctic Ocean. A conclusion is drawn that plumes are a special case of mantle-lithospheric flows, which according to deep geophysics are often located horizontally which leaves out their plume origin. Heated masses of mantle substance under young volcanic regions or rift zones of mid-ocean ridges do not emerge from the depth in the form of a straight column, but rather have arbitrary shapes, skewing to the sides and having outgrowths, offshoots, spherical bulges. Vertically rising flows of hot magma (plumes) are not a cause, but an effect of a lithospheric split and rise of magmatic substance due to decompression. A conclusion is made that it is unproductive to exaggerate the shapes and sizes of plumes and use them to explain all the diversity of endogenous processes.
Keywords: plume tectonics; mantle-lithospheric flows; Hawaiian islands; Iceland; large igneous provinces